Fundamental of Intrepreneurship (ENT300) : Athletes Rehabilitation (AR7) / Dayang Nurul Hanadira Elpis... [et al.] - Elpis, Dayang Nurul Hanadira; Zulkifli, Hafizah; Alet, Mohamad Arif Zulhilmi; Safri Waldi, Effiqri Firqin; Sarbini, Mohd Shahrol Haqimi; Mudihi, Izzat Al Wale; Arin, Ina (2015)
AR7 is a partnership company that is generally known as rehabilitation service in Kuching and Kota Samarahan. AR7 will be providing best quality of service to our customers. We are ready to make our customers be satisfied with the services provided. Our company consists of seven members whereby all the members are giving their supports to the project. All the members contribute the same amount of capital. The reason we chose rehabilitation service because due to a high demand from customers especially athletes around Kuching and Kota Samarahan. Another reason it is because of its strategic location, other than it is located near to the main road.